THE POSITION OF THE ULAMA CONSULTATIVE COUNCIL IN THE ACEH GOVERNMENT POLICY - Husni Jalil; Teuku Ahmad Yani; Andri Kurniawan (Universitas Syiah Kuala, 2023)
This article explains the position of the Ulama Consultative Council (Majelis Permusyawaratan Ulama/MPU), as recognized under the Aceh Qanun number 13, year 2017, which places MPU as a partner of the governor, regents, mayors, and local parliaments. The MPU has the authority to provide commentaries on legislative products (Qanun) and other regional policies. However, this strategic position is constrained by several factors i.e., the lack of legislative knowledge. Meanwhile, the implementing agencies within the MPU structure cannot support MPU's performance. Aceh Qanun Number 13 of 2017 concerning the MPU's Procedure for Providing Commentaries is not in sync with Aceh Qanun Number 5 of 2011 concerning Procedures for Qanun Preparation. This Qanun has not accommodated the MPU's authority to provide commentaries. The provisions contained in the Qanun refer to the provisions for legislative preparation regulated by the central government and do not accommodate Aceh's local wisdom. The local parliamentary rules have not authorized the MPU to provide commentaries at each parliamentary stage of the Qanun preparation process, as it is only refers to legislative preparation provisions under national or central legislations.